Brainstorming Implementation on Students’ Difficulties in Listening Skills - Irmawaty Hasyim; Salmia Syarifuddin (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2025)
The aim of this research was to describe how the brainstorming technique worked in improving students’ difficulties in comprehending listening audio recordings in a listening class. Brainstorming was the process of generating new ideas without criticizing or evaluating those ideas during the class session to encourage students to participate freely and spontaneously in class discussion. As a result, the class atmosphere became relaxed, and students felt free and ready to follow the listening session. Brainstorming techniques involved pre-listening activities as well as while-listening and post-listening activities. In this research, the results of this free discussion were reflected in students’ free-writing tasks about their learning experiences in listening skills. This research applied a descriptive qualitative method, in which writing data were obtained from 24 students who attended a listening class in their first year in the 2024–2025 academic year. The research instruments were texts, audio recordings, and written observation sheets.